2013
DOI: 10.1080/00986445.2012.757549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SDS on the Dispersion Stability of Ysz Particles in an Electroless Nickel Solution

Abstract: Optimum particle dispersion is an essential feature for composite coatings carried out on the autocatalytic electroless nickel plating platform. In this regard, the potential influence of an anionic surfactant, sodium dodecyl sulphate (SDS), on the dispersion stability of a ceramic, yttria stabilized zirconia (YSZ), in an acidic electroless nickel solution of pH 4.9 has been assessed in this study. Ultra violet-visible spectrophotometry was used in accordance with the Beer-Lambert law (-log (I 1 = I 0 ) ¼ A) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…1a, b and the values obtained are -12.97 and -8.04 mV respectively. The negative value of zeta potential indicates the negative surface charge on the SDS treated ceramic particles which arise due to electrostatic interactions between the surface of ceramic particles and the SDS molecules in aqueous solutions at lower temperature [16,17]. This behaviour suggested that the negatively surface charged particles hinder agglomeration and further favoured the uniform distribution of ceramic particles in DMF solvent.…”
Section: Resultsmentioning
confidence: 99%
“…1a, b and the values obtained are -12.97 and -8.04 mV respectively. The negative value of zeta potential indicates the negative surface charge on the SDS treated ceramic particles which arise due to electrostatic interactions between the surface of ceramic particles and the SDS molecules in aqueous solutions at lower temperature [16,17]. This behaviour suggested that the negatively surface charged particles hinder agglomeration and further favoured the uniform distribution of ceramic particles in DMF solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently particles incorporation into the nickel matrix become more uniform and in some cases even the porosity of the coatings can be reduced [16,22]. It should be noted that the optimum concertation of SDS should be used, otherwise excess SDS will exert detrimental effect on the coating [23,22,24]. An Aldrich silicon nitride (Si 3 N 4 ) powder was chosen for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Many industries benefit from the use of electroless Ni deposits including oil and gas, automotive, electronics, microelectronics, aerospace and decoration [1,2]. Electroless Ni deposits are produced by the autocatalytic electrochemical reduction of nickel ions from the plating solution by means of a chemical redox [3,4].…”
Section: Introductionmentioning
confidence: 99%